1957
DOI: 10.1002/jsfa.2740080902
|View full text |Cite
|
Sign up to set email alerts
|

Cacao glycosidase and colour changes during fermentation

Abstract: The first stage in the destruction of the anthocyanin pigments in cacao beans during the curing treatment is hydrolysis by a glycosidase. The relevance of this reaction to the quality of the processed bean is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
8

Year Published

1963
1963
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 8 publications
1
14
0
8
Order By: Relevance
“…Processing of cocoa on the farms begins with the opening of the fruit (pods) in the field under the trees, where the seeds are separated from the husks. The seeds are then fermented in wooden boxes and sun-dried, to be later processed in the factory (Forsyth and Quesnel, 1957;Kalvatchev et al, 1998;Camu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Processing of cocoa on the farms begins with the opening of the fruit (pods) in the field under the trees, where the seeds are separated from the husks. The seeds are then fermented in wooden boxes and sun-dried, to be later processed in the factory (Forsyth and Quesnel, 1957;Kalvatchev et al, 1998;Camu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A fermentação é uma etapa essencial para a obtenção de amêndoas de boa qualidade, devido a complexas reações bioquímicas que provocam a morte do embrião, hidrólise de açúcares e proteínas, liberação de enzimas e substratos, difusão de compostos fenólicos que entram em contato com as enzimas, entre outras (FORSYTH;QUESNEL, 1958;BECKETT, 1994;BRITO, 2000;EFRAIM, 2004 (BRITO, 2000). Durante a fermentação das sementes, uma das primeiras etapas do processamento para obtenção de derivados de cacau, ocorre a morte do embrião ou gérmen.…”
Section: Introductionunclassified
“…This is contrary to what has been reported (Crozier et al, 2011), since positive correlations have been found between polyphenol content and astringent taste. This lack of total correlation may be explained by the fact that in some samples, roasting promoted greater oxidation of phenolic compounds (quantified in unfermented seeds), consequently greater formation of quinones derived from some polyphenols such as catechins, epicatechins, and condensation of proteins, resulting in reduced astringency and bitter taste (Forsyth & Quesnel, 1957).…”
Section: Resultsmentioning
confidence: 99%